1989
DOI: 10.1115/1.3243648
|View full text |Cite
|
Sign up to set email alerts
|

Pipe Flow Measurements of a Transparent Non-Newtonian Slurry

Abstract: An experimental description of the flow structure of non-Newtonian slurries in the laminar, transitional, and full turbulent pipe flow regimes is the primary objective of this research. Experiments were conducted in a large-scale pipe slurry flow facility with an inside pipe diameter of 51 mm. The transparent slurry formulated for these experiments from silica, mineral oil, and Stoddard solvent exhibited a yield-power-law behavior from concentric-cylinder viscometer measurements. The velocity profile for lamin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
28
0
1

Year Published

1992
1992
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 0 publications
6
28
0
1
Order By: Relevance
“…Lenoble et al (2005a) and Wiederseiner (2010) measured the velocity profiles in a rheometer (in a parallel-plate and a wide-gap Couette cell, respectively). Averbakh et al (1997), Koh et al (1994), Lyon and Leal (1998a, b), Park et al (1989), Shauly et al (1997), and Zisselmar and Molerus (1979) observed the flow of concentrated slurries in pipes. Wildman et al (1992) looked at pipe contraction flows.…”
Section: Fluidized Beds and Particle Suspensionsmentioning
confidence: 96%
“…Lenoble et al (2005a) and Wiederseiner (2010) measured the velocity profiles in a rheometer (in a parallel-plate and a wide-gap Couette cell, respectively). Averbakh et al (1997), Koh et al (1994), Lyon and Leal (1998a, b), Park et al (1989), Shauly et al (1997), and Zisselmar and Molerus (1979) observed the flow of concentrated slurries in pipes. Wildman et al (1992) looked at pipe contraction flows.…”
Section: Fluidized Beds and Particle Suspensionsmentioning
confidence: 96%
“…The test cases considered for this article. The first two are from Slatter [13], PARK1 is from Park et al [48], and the last two belong to experimental data supplied by the co-authors [49]. [49] In all simulations, the length of the pipe was set to L = 30 to 45 m (longer for a thicker pipe, L D > 300) to ensure that the flow reached a fully developed state and to avoid interference from the outflow boundary.…”
Section: Meshmentioning
confidence: 99%
“…The error in the rheological measurements is a maximum of 1.46% [50]. Park et al [48] mention that their rheological parameters were obtained by linear regression of viscometric data, with a coefficient of determination of 0.996.…”
Section: Meshmentioning
confidence: 99%
“…Park et al [5] used laser techniques to investigate the turbulent structure of nonNewtonian slurries. Higher intensities were observed in the wall region when compared with that of air.…”
Section: Evidence Of Particle Roughnessmentioning
confidence: 99%